Criminal achievement, criminal self-efficacy, and the criminology of Carlo Morselli: suggestions for continuing and extending a fruitful line of inquiry - Brezina, Timothy (Global crime, 2022)
The unique scholarship of Carlo Morselli fuelled interest in criminal networks, entrepreneurship, and achievement. In this paper, we summarise Morselli’s contributions to the scholarship on criminal achievement, with special attention to the subjective aspects of such achievement. We show how Morselli’s work ignited interest in the novel concept of criminal self-efficacy and we offer a number of suggestions for continuing and extending this important line of work. In particular, we (1) discuss reasons why the subjective aspects of criminal achievement have been largely neglected by others, but why they are important to explore; (2) review the possible sources of criminal self-efficacy; (3) discuss gender differences in this area; and (4) highlight the overall balance between criminal and conventional self-efficacy as an important consideration. Further research in this area may help us better understand the attraction to crime, the limited effectiveness of punishment, and reasons for the persistence of criminal careers.